Environmental Disclosure Memediasi Green Accounting Dan Sustainable Development Terhadap Green Economy - Heriyah, Heriyah (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2023)
ABSTRACT This research aims to analyze the impact of implementing green accounting and sustainable development on the green economy with environmental disclosure as a mediated variable. The negative impact on the environment which results in environmental pollution and results in organisms around the environment becoming damaged is one of the objectives of this research. The population used in this research is mining sector companies listed on the Indonesia Stock Exchange in 2017-2022. The research sampling method used purposive sampling, totaling 27 companies and the type of data used was secondary data in the form of annual reports. The data testing technique uses the classic assumption test with the data analysis method used, namely the extension path of simple regression analysis and the coefficient of determination. The research results show that green accounting has no effect on the green economy, sustainable development has an effect on the green economy, green accounting and sustainable development has an effect on the green economy both before and after environmental disclosure as a mediated variable.